HUBUNGAN PENDAPATAN DAN PENDIDIKAN ORANG TUA DENGAN HASIL BELAJAR GEOGRAFI SISWA KELAS XI SMA N 1 ULAKAN TAPAKIS KABUPATEN PADANG PARIAMAN TAHUN PELAJARAN 2021/2022 - Susanti, Cendy; Ahyuni, Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
This study aims to determine whether there is a relationship between income and parental education on student learning outcomes. This type of research is quantitative with Multiple Linear Regression Method. The population of this research is the students of class XI majoring in Social Studies in the academic year 2021/2022 as many as 80 students with a sample of 80 students using